2020
DOI: 10.5606/archrheumatol.2020.7294
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Latent Tuberculosis in Children With Immune-Mediated Inflammatory Diseases Treated With Anti-Tumor Necrosis Factor Therapy: Comparison of Tuberculin Skin and T-SPOT Tuberculosis Tests

Abstract: Objectives: This study aims to analyze the coherence between T-SPOT tuberculosis test (T-SPOT.TB) and tuberculin skin test (TST) with different cutoff values in screening latent tuberculosis infection (LTBI) both prior to and at the sixth month of anti-tumor necrosis factor (anti-TNF) treatment. Patients and methods: This prospective multicentric study included 57 children (34 girls, 23 boys, mean age 12.4±3.9 years; range, 6 to 18 years) diagnosed with immune-mediated inflammatory diseases (IMIDs) evaluated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Similarly, in a study conducted by Kılıç et al with 144 children receiving anti-TNF in our country, they reported the rate of LTBI as 4.8% (13). Girit et al reported the rate of LTBI before treatment as 28.1% in their study with 57 cases (14).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Similarly, in a study conducted by Kılıç et al with 144 children receiving anti-TNF in our country, they reported the rate of LTBI as 4.8% (13). Girit et al reported the rate of LTBI before treatment as 28.1% in their study with 57 cases (14).…”
Section: Discussionmentioning
confidence: 53%
“…Similarly, the rate of tuberculosis development was reported as 0.85% by Çağatay et al, and 1.5% by Hanta et al(18,19). Contrary to these studies, Girit et al and Kurt et al reported that tuberculosis did not develop in any of the patients receiving anti-TNF (14,20). Con icting results have been reported in studies examining the bene t of prophylaxis for LTBI.…”
Section: Discussionmentioning
confidence: 92%
“…Current literature comparing the performance of IGRA (Quantiferon and T-Spot) and TST to identify TB infection in young children reveals limited evidence and conflicting results [5,[30][31][32][33]. Studies focusing on performance of T-Spot in comparison to TST may show discordant results with TST positive and T-Spot negative cases.…”
Section: Viability Of T-spot In Contact Infantsmentioning
confidence: 99%
“…Several guidelines recommend chest X‐ray, tuberculin skin test (TST), and history taking regarding contact with persons with TB for LTBI screening 15,16 . TST is the most common method of bacillus Calmette‐Guerin (BCG) vaccination evaluation and is the most commonly used test for the diagnosis of LTBI.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Several guidelines recommend chest X-ray, tuberculin skin test (TST), and history taking regarding contact with persons with TB for LTBI screening. 15,16 TST is the most common method of bacillus Calmette-Guerin (BCG) vaccination evaluation and is the most commonly used test for the diagnosis of LTBI. However, the diagnosis of LTBI with TST has a number of difficulties, particularly in children who have received BCG vaccination.…”
mentioning
confidence: 99%